Wither International Law? Security Certificates, the Supreme Court, and the Rights of Non-Citizens in Canada - Hudson, Graham (Refuge: Canada's Journal on Refugees, 2010)
In this paper, the author examines the role of international law on the development of Canada’s security certificate regime. On the one hand, international law has had a perceptible impact on judicial reasoning, contributing to judges’ increased willingness to recognize the rights of non-citizens named in certificates and to envision better ways of balancing national security and human rights. On the other hand, the judiciary’s attitudes towards international law as non-binding sources of insight akin to foreign law has reinforced disparities in levels of rights afforded by the Canadian Charter of Rights and Freedoms and those afforded by international human rights. Viewed skeptically, one might argue that the judiciary’s selective result-oriented use of international law and foreign law helped it spread a veneer of legality over an otherwise unaltered and discriminatory certificate regime. Reviewing Charkaoui I and II in international context, the author suggests an alternative account. He suggests that the judiciary’s use of international law and foreign law, although highly ambiguous and ambivalent, both was principled and has progressively brought named persons’ Charter rights more closely in step with their international human rights. Although the current balance between national security and human rights is imperfect, the way in which aspects of Canada’s certificate regime have been improved suggests that international law is a valuable resource for protecting the rights of non-citizens in Canada.